University-Society Linkages as a Catalyst for Scientific Research: Analysis of their Impact on the Production of Socially Relevant Knowledge. - Pancorbo Sandoval, Jose Armando; Leyva Ricardo, Sonia Emilia; Barba Mosquera, Ángela Elena; Erazo Rivera, Renato Patricio (Conexiones UG, 2025)
The study examines the relationship between university-society engagement and scientific research, focusing on the role of student researchers. The research analyzes how this convergence drives the generation of knowledge with impact on regional development[MO1.1], particularly in environmental sustainability projects. The results show a dual impact: the production of scientific research aligned with territorial needs and the development of innovative solutions for local problems. The model strengthens the quality of produced knowledge while enriching student training and reinforcing the university’s role as an agent of social change. It concludes that this approach is effective in developing socially relevant scientific research while training researchers committed to regional development.
Keywords: University-society engagement; Scientific research; Regional development; Environmental sustainability; Social innovation